STRES PADA KEJADIAN STROKE - Gabriella Adientya; Fitria Handayani (Jurnal Keperawatan Diponegoro, 2012)
Stroke is the third largest cause of death in the world with a mortality rate of 18 - 37%, stroke risk factors were related to one of them is stress. Treatment of stress need to be prioritized, because the health department in 2008 report about 10% of the entire population of Indonesia is stressed. The purpose of this study was to determine the stress on the incidence of stroke. This study used a descriptive correlational research design with cross-sectional approach nonprobability sampling and sampling with purposive sampling techniques and data analysis using univariate tests. The number of samples is 90 respondents stroke and recurrent stroke. Techniques of data collection using questionnaires Depression Anxiety Stress Scale 42 (DASS 42), with significant <α (0.05) given to patients with no recurrent stroke and recurrent stroke. The results of stress analysis of research data on the incidence of stroke, found no recurrent stroke 50 respondents (55.6 %) consisting of 13 respondents (26 %) no stress, 19 respondents (38 %) mild stress, 14 respondents (28 %) and the stress is 4 respondents (8 %) of severe stress. 40 respondents experienced recurrent stroke (44.4%) which includes 6 respondents (15 %) no stress, 11 respondents (27 %) mild stress, 14 respondents (35 %) and 9 respondents were stress (22.5%) of severe stress. The conclusion of this study a total of 71 respondents (78.9 %) experienced stress. Suggestions for hospitals, nursing care provided nurses can be directed to controlling the risk factors stress